Deconstructing the boundary between environmental sustainability and social justice: decision-making and obscured rationalities in government-led housing in Johannesburg - Fatti, Christina Culwick (Department of Environmental and Geographical Science, 2025)
The idea of ‘just sustainability', which is based on the aspiration of aligning social justice and environmental sustainability imperatives, has become a focus among scholars and practitioners in addressing contemporary social and environmental crises. Despite claims that environmental sustainability and social justice can coexist, reconciling these goals proves challenging in theory and practice. The disjuncture between policy commitments and the practical achievement of just sustainability is rooted in the need for deeper engagement with how the boundary space between social justice and environmental sustainability is theorised. There's a growing acknowledgement among scholars of the need for a nuanced understanding of this boundary space for identifying trade-offs and understanding how conflicting rationalities impact decision-making within cities. Given that urbanisation, poverty, and climate change impacts are concentrated in cities in the global South, the challenge of building socially just and environmentally sustainable cities predominantly lies with Southern cities. As a coalescing point for infrastructure and urban development, government-led housing has been linked explicitly to building just and sustainable cities. South Africa's government housing programme is responsive to both environmental sustainability and social justice concerns through improving access to shelter and basic services, and facilitating access to amenities and opportunities. However, there is little consensus among scholars or practitioners regarding how government in South Africa should balance the immediate need for housing while addressing unsustainable and unjust urban forms, resource constraints and high levels of inequality. This project uses government-led housing in Johannesburg, South Africa, to examine the boundary space between social justice and environmental sustainability, and how knowledge and decision-making interact with this space. The study first examines the practical outcomes of government-led housing. Second, it considers the policy and decision-making processes involved in developing government-led housing projects, and third, it interrogates the theoretical challenge of bringing social justice and environmental sustainability together in Southern cities. This multidisciplinary study, which uses two case studies, Lufhereng and Pennyville housing projects, employs various analytical and data collection methods, incorporating qualitative and quantitative approaches, to undertake a dynamic assessment of government-led housing outcomes and decision-making processes. This research innovatively combines photo essays with traditional research methods, creating a unique synergy between objective and subjective perspectives on government-led housing projects. By underscoring the intricate interplay between justice and sustainability in government-led housing projects, instances are revealed where outcomes are aligned in some instances and conflictual in others. The research argues that linear, reductionist relationships between social justice and environmental sustainability are unhelpful in building nuanced understandings of the interaction between these imperatives. Furthermore, Watson's (2003) concept of conflicting rationalities, which represents irreconcilable perspectives, is extended and applied in new ways. The idea of ‘obscured rationalities' is developed to denote subtle conflicts within decision-making processes, and how these can influence outcomes, rather than obvious conflicts, such as those between social justice and environmental sustainability. The argument is made that developing nuanced understandings of the interplay between social justice and environmental sustainability is crucial for theory development, policymaking, and practical outcomes. Highlighting uneven knowledge approaches and addressing this through expanding theorisation from the global South is necessary for realigning the structural elements leading to inequality and unsustainability.